Comet and cytogenetic tests as tools for evaluating genomic instability in seeds of Oryza sativa L. and Phaseolus vulgaris L. from gene banks - Dantas, Alisson F. (2018)
This study aimed to assess the feasibility of comet and cytogenetic tests as tools for evaluating genomic instability in seeds of Oryza sativa L. (rice) and Phaseolus vulgaris (beans) L. from gene banks. Rice and beans were exposed to methyl methanesulfonate (MMS) as a reference DNA damaging agent. Seeds of two accessions of rice and beans were obtained from Embrapa Rice and Beans - Brazil. Seed groups were imbibed in three concentrations of MMS for three periods of time to carry out cytogenetic tests, and for one period for the comet test. At concentrations of 10 and 15 mg/L, MMS induced cytotoxic and/or mutagenic effects in the meristematic cells of roots from all the accessions of both species. In the comet test, MMS induced genotoxic effects at all the concentrations in the evaluated accessions of rice and beans, except in one accession of beans at the lowest concentration (5 mg/L). Both species showed sensitivity to MMS. The comet test can be proposed for the measurement of genomic instability in accessions of rice and beans in gene banks, as being more sensitive than the cytogenetic tests used.